Bronchial epithelial cell transcriptome shows endotype heterogeneity of asthma in patients with NSAID-exacerbated respiratory disease - Jakiela, Bogdan; Soja, Jerzy; Sladek, Krzysztof; Przybyszowski, Marek; Plutecka, Hanna; Gielicz, Anna; Licholai, Sabina; Aab, Alar; Rebane, Ana; Bochenek, Grazyna (Journal of allergy and clinical immunology, 2023)
Nonsteroidal anti-inflammatory drugs–exacerbated respiratory disease (N-ERD) is currently classified as a type-2 (T2) immune-mediated disease characterized by asthma, chronic rhinosinusitis, and hypersensitivity to cyclooxygenase-1 inhibitors. The aim of this study was to characterize immunological endotypes of N-ERD based on the gene expression profile in the bronchial epithelium. mRNA transcriptome (mRNA-sequencing) was analyzed in bronchial brushings from patients with N-ERD (n = 22), those with nonsteroidal anti-inflammatory drug–tolerant asthma (NTA, n = 21), and control subjects (n = 11). Additionally, lipid and protein mediators were measured in bronchoalveolar lavage fluid (BALF). Initial analysis of the entire asthma group revealed 2 distinct gene expression signatures: “T2-high” with increased expression of T2-related genes (eg, CLCA1, CST1), and “proinflammatory” characterized by the expression of innate immunity (eg, FOSB, EGR3) and IL-17A response genes. These endotypes showed similar prevalence in N-ERD and NTA (eg, T2-high: 33% and 32%, respectively). T2-high asthma was characterized by increased expression of mast cell and eosinophil markers, goblet cell hyperplasia, and elevated LTE4 and PGD2 in BALF. Patients with a proinflammatory endotype showed mainly neutrophilic inflammation and increased innate immunity mediators in BALF. Furthermore, the proinflammatory signature was associated with a more severe course of asthma and marked airway obstruction. These signatures could be recreated in vitro by exposure of bronchial epithelial cells to IL-13 (T2-high) and IL-17A (proinflammatory). T2-high signature was found only in one-third of patients with N-ERD, which was similar to what was found in patients with NTA. The proinflammatory endotype, which also occurred in N-ERD, suggests a novel mechanism of severe disease developing on a non-T2 background.